Isolation and Identification of Bacteria Producing Antibiotic Compounds from The Rhizosphere of Avicennia Marina Against Pathogenic Bacteria in The Mangrove Ecosystem Area of West Kalimantan - Khairillah, Yuyun Nisaul; Alang, Hasria; Haryanto, Haryanto; Fitriagustiani, Fitriagustiani; Erwhani, Indri; Purnamawati, Ditha Astuti; Rahmawati, Annisa; Surtikanti, Surtikanti; Triwahyuni, Adelia (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
Antibiotic resistance is a global problem in the health sector. The level of antibiotic resistance that occurs can be caused by several influencing factors, including 6 isolates of rhizosphere bacteria that were successfully isolated from the rhizosphere of the Avicenia marina plant. The purpose of this study was to isolate and determine the best minimum inhibitory concentration of rhizosphere bacteria of the A. marina plant and its effectiveness in inhibiting pathogenic bacteria S. aureus. This study is a quantitative research method using the isolation and characterization of rhizosphere bacteria, antagonistic test of rhizosphere bacteria and test of the results of the extraction of filtrate of rhizosphere bacteria culture of A. marina plants. The results of this study were (1) five of the isolates of bacteria that were successfully isolated were included in the Bacilus type and 1 isolate of bacteria included in the Cocobasil type; (2) there were 3 of the 6 isolates that could inhibit the growth of pathogenic bacteria S. aureus with an inhibition range of 10.04-4.42 mm; (3) Rhizosphere bacterial isolate (TN 1) is an isolate with the best inhibition diameter and is categorized as strong, namely 10.04 mm; (4) ethyl acetate extract of Rhizosphere bacterial isolate culture filtrate (TN 1), has a minimum inhibitory concentration of 0.50% against pathogenic bacteria S.aureus with an inhibition diameter of 7.18 mm which is better when compared to the positive control using chloramphenicol.